Tuning fork UWB antenna with unsymmetrical feed line - Alam, A. H. M. Zahirul; Islam, Md. Rafiqul; Khan, Sheroz (2012)
A simple planar rectangular UWB is designed with unsymmetrical feed line. It is observed that the unsymmetrical feed line plays an important role for increasing the antenna bandwidth. The rectangular planer antenna is then modi¯ed to tuning fork shaped without sacri¯cing the bandwidth of the antenna. By removing portion of conductive plane from the rectangular patch to makes tuning fork shaped antenna creates additional resonance, thus enhance the bandwidth of the antenna. The open space of the antenna can be utilized for placing other components. The fabricated antenna satis¯es the 10-dB return loss requirement from 3.8 GHz to more than 15 GHz. The overall dimension of the antenna is 40 £ 40 £ 1:6mm3. The proposed antenna has a simple con¯guration and is easy to fabricate. Experimental results show that the proposed antenna could be a good candidate for UWB application.